Assessing Innovation Potential of the Agricultural Enterprise - S. P. Burlankov; S. A. Kuzmin (Вестник Российского экономического университета имени Г. В. Плеханова)
The article discusses different academic views on the assessment of innovation potential of the enterprise. Opinions of scientists in the field of management and assessment of the enterprise innovation potential served as a methodological foundation of the research. Researchers dealing with issues of innovation potential management developed qualitative and quantitative methods of potential estimation and formulated approaches to its assessment. The authors support the quantitative approach to assessment and estimation of innovation potential, therefore indicators have mainly mathematic expression. By studying methods of enterprise innovation potential estimation systematization of approaches was carried out. Different authors classified methods of estimation depending on needs of the market environment and on conceptual characteristic of the potential. The article revealed that the optimal methodology of estimation and management of innovation potential had not been formulated, thus we need approaches based on integral qualitative indicators, which can characterize the innovation potential.